A domain-specific language to specify behavior in a management game simulator (2011)
The contribution of this thesis is the use of the DSL approach in a real-world context (and not only as a case study), consisting on a domain-specific transactional system with a large number of functional requirements (with about70different business decisions) that can change through the time and whose size rises 800.000 LOCs. Finally, the whole project implementation is evaluated empirically through a validation workshop done by all of the targeted users(the MAGES developers). The advantages gained, and the issues faced could certainly serve as a reference case for other projects.